2010
DOI: 10.1002/hec.1529
|View full text |Cite
|
Sign up to set email alerts
|

Non‐pecuniary returns to higher education: the effect on smoking intensity in the UK

Abstract: This paper investigates whether higher education (HE) produces non-pecuniary returns via a reduction in the intensity of consumption of health-damaging substances. In particular, it focuses on current smoking intensity of the British individuals sampled in the 29-year follow-up survey of the 1970 British Cohort Study. We estimate endogenous dummy ordinal response models for cigarette consumption and show that HE is endogenous with respect to smoking intensity and that even when endogeneity is accounted for, HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
6
0
2
Order By: Relevance
“…Education is also well understood to be associated with time preference. This point has been raised by Sander (1995), Bratti and Miranda (2010) and references therein in the context of smoking margins, and by Fuchs (1982) and van der Pol (2011) in a more general setting. Disentangling the true association between education and drinking behaviour requires therefore to account for this possible source of omitted variable bias.…”
Section: The Effect Of Compulsory and Higher Education On Drinking Bementioning
confidence: 92%
“…Education is also well understood to be associated with time preference. This point has been raised by Sander (1995), Bratti and Miranda (2010) and references therein in the context of smoking margins, and by Fuchs (1982) and van der Pol (2011) in a more general setting. Disentangling the true association between education and drinking behaviour requires therefore to account for this possible source of omitted variable bias.…”
Section: The Effect Of Compulsory and Higher Education On Drinking Bementioning
confidence: 92%
“…Studies have found a relationship between a higher level of education and a greater use of preventive treatments and specialist health care, as well as a greater attention to chronic health problems (Feinstein, Sabates, Anderson, Sorhaindo and Hammond, 2006). In addition, a higher level of education has been related to a series of behaviours that impact health, such as being less likely to smoke or more likely to smoke fewer cigarettes (Bratti and Miranda, 2009), a lower probability of alcohol abuse (Escardíbul and Calero, 2006), a greater propensity for physical exercise and of maintaining a balanced diet (Feinstein et al, 2006). A relationship has also been identifi ed between level of education and chosen place of residence (Wolfe and Zuvekas, 1997), which impacts health as a result of general living conditions, air pollution and the probability of having an accident (Feinstein et al, 2006).…”
Section: The Non-monetary Effects Of Education: An Overviewmentioning
confidence: 99%
“…En particular, es posible distinguir 4 tipos de situaciones en relación a la posible endogeneidad de la variable explicativa (Bratti y Miranda, 2010):…”
Section: El Problema De La Endogeneidadunclassified